Pathological, Bacteriological and Prevalence Studies Of Ovine Footrot - Al-Jashamy, Karim Alwan Mohamed (2003)
Ovine footrot, is a disease associated with infection by the bacterium Dichelobacter nodosus. It is a disease that limits the productivity or sheep-farming enterprises throughout the world. Both wool production and body weight are adversely affected during the clinical phase of the infection. Ovine footrot has become an important contagious disease in Malaysia. The first confirmed case of footrot was reported in a government sheep farm in mid-198Os. The disease is now present ill other farms throughout the country, and local vaccine is being used to reduce the disease. Previous studies have identified D. nodosus in three sheep farms ill Malaysia and only serogroup B was identified. The possible presence of other D. nodosus serogroups and scrotypes is unknown. This study attempts to isolate and identify the unknown serogroups and serotypes so as develop a better vaccine candidate using local isolates of D. nodosus. Eight sheep farms were investigated in this study. Four sheep farms were found to be infected with D. nodosus. Two hundred and ninety-three D. nodosus isolates were obtained from 741 foot samples. Five serogroups were identified in Malaysia. This is the first study where serogroups A, C, F and I with their serotypes AI, A2, CI, FI and F2 were identified in the infected sheep farms. Serogroup B was the predominant serogroup isolated (78.2%) while the isolation percentages for serogroups F, A, I and C were 7.9%, 7.5%, 3.8% and 2.7% respectively. The information on the pathogenesis of the disease is still lacking despite previous studies on ovine footrot. Interdigital cutaneous changes associate with footrot in sheep is not well documented. The disease was induced experimentally in sheep by topical application of bacterial isolates on the interdigital skin of the hoof, and light and electron microscopy studies of the lesions were conducted. Virulent footrot was observed by a gross progressive separation of the horny tissues from the soft tissues. On day 21 post inoculation (p.i.), a complete separation of the hoof from the underrunning structures and lameness were evident. The benign footrot was observed with mild interdigital dermatitis and all infected feet completely recovered on day 21 p.i.. Histopathological changes in virulent footrot were observed in the interdigital skin layers and hoof matrix. These ranged from acute dermatitis to hyperkeratosis, parakeratosis and acanthosis of the epidermis. Oedema and leukocytic infiltration with neutrophils, macrophages and scanty lymphocytes were also evident in the dennis. Furthermore, vasculitis and perivascular cuffing, lymphangitis and inflammation of the sweat glands were observed in the dermis. The histopathological changes of benign footrot were less severe than virulent form in the epidermis and there were no pathological changes in the dermis. In scanning electron microscopy, a severe zone of lysis appearing as a surface depression around bacteria in the horny layer of the interdigital skin of the hoof was detected in virulent footrot, while this lesion was less severe in the benign form. Transmission electron microscopy revealed degeneration in the epiderm is and dermis. Degeneration in the basal cell layer of the epidermis and the basement membrane in virulent form of footrot, which have not been reported previously was observed in this study. Dichelobacter nodosus was observed in the lesions of the epidermis and dermis of virulent footrot. Its' isolation from characteristic foot lesions indicated that it was associated with footrot. Immunohistochemistry observations validate the relationship between the lesions seen in footrot and virulent D. nodosus. Immunogold staining technique facilitates to detection and localisation of D. nodosus for electron microscopy. Specific reactions were labelled in components and the matrix of epidermis and dermis of the interdigital skin. Dichelobacter nodosus antigen labelled with 5 nm gold particles was observed in the intracellular and intercellular spaces of the epidermis. This is the first report where immunogold labelling technique have been used in the study of footrot lesions in sheep for electron microscopical observations. The total monthly rainfall and mean daily temperature have a relation to the prevalence rate of the disease. These conditions provide suitable environment propagation of D. nodosus. The overall prevalence of footrot in the eight farms investigated was 3.3%. The highest prevalence was recorded in April (0.8%), while the lowest in August (0.3%) in IHK farm by survey study. Observations described in this study were made to define the prevalence are related to seasonal conditions, but the effect of rainfall overrides all other factors for footrot to occur. Adults were more susceptible than weaners. No cases were detected in preweaners. The prevalence by sex which was 4.4% in the male and 7.7% in the female was significant (p=O.009). No significant difference in prevalence rates between breeds was detected.